A Content Analysis of the Vision Statements of Top 10 Leading Universities in Indonesia: Analisis Isi Pernyataan Visi 10 Universitas Terkemuka di Indonesia - Suteki, Mega; Wicaksono, Aries Samudra; Ama Longgy, Dodhy Hyronimus; Adiatma, Tini (STAI Publisistik Thawalib Jakarta, 2024)
This study analyzes the vision statements of Indonesia's top 10 universities, as ranked by Times Higher Education in 2024. Vision statements are crucial for defining a university’s strategic direction, identity, and stakeholder engagement. The content analysis identifies recurring themes, including scientific advancement, innovation, community empowerment, and global competitiveness. While these statements articulate ambitious goals, potential challenges such as symbolic rhetoric and institutional isomorphism may hinder their effectiveness. The findings emphasize the need for vision statements that are actionable and aligned with the institution's mission. The study concludes with recommendations for further research on the practical implementation of these visions and the role of leadership, as well as strategies for embedding visions into institutional culture.